Subepicardial dysfunction leads to global left ventricular systolic impairment in patients with limb girdle muscular dystrophy 2I. (September 2013) - Hollingsworth, Kieren G.; Willis, Tracey A.; Bates, Matthew G.D.; Dixon, Ben J.; Lochmüller, Hanns; Bushby, Kate; Bourke, John; MacGowan, Guy A.; Straub, Volker
<x xml:space="preserve">Abstract</x> Aim The mechanisms of cardiac dysfunction in limb girdle muscular dystrophy 2I (LGMD2I) are unclear. This study assessed deficits in cardiac morphology, function, and metabolism quantitatively in patients with a confirmed genetic diagnosis of the homozygous c.826C > A FKRP (fukutin‐related protein) mutation, using a comprehensive magnetic resonance (MR) examination. Methods and results Ten patients (7 male and 3 female) and 10 matched control subjects were recruited prospectively. Cardiac morphology by cine imaging, cardiac torsion and strain by MR tagging, and cardiac energetics by phosphorus‐31 MR spectroscopy were measured. LGMD2I subjects were found to have a significant reduction in peak cardiac torsion (3.9 ± 1.3° vs. 6.4 ± 1.5°, P = 0.04), and in the ratio of torsion to endocardial strain (0.31 ± 0.05 vs. 0.51 ± 0.14, P = 0.03), compared with control subjects. The impairment in torsion correlated strongly with reduction in EF (r = 0.93, P < 0.001). Peak circumferential and longitudinal strains were preserved in the patients, however [LGMD2I, 16.4 ± 3.2% vs. 18.3 ± 3.5%, non‐significant (NS); and LGMD2I, 17.0 ± 3.0% vs. 18.4 ± 3.5%, NS]. Cardiac cine analysis demonstrated reduced EF (47 ± 7% vs, 58 ± 4%, P = 0.02) and stroke volume (61 ± 11 mL vs. 81 ± 13 mL, P = 0.04), though no evidence of LV hypertrophy was found. The ratio of phosphocreatine to ATP (PCr/ATP) was reduced in the LGMD2I subjects compared with controls (1.50 ± 0.24 vs. 1.94 ± 0.12, P = 0.0001). Conclusions The loss of torsion with preservation of circumferential and longitudinal strain in LGMD2I is a unique finding and suggests subepicardial dysfunction with abnormal transmission of force across the cardiac wall.